Cost-effective drying methods for edible bird’s nest hydrolysate: Impact on nitrite levels and sialic acid content - Yeo, Bee Hui; Anamaly, Mithula; Lai, Oi Ming (Malaysian Society For Molecular Biology & Biotechnology, 2024)
To produce powdered edible bird’s nest hydrolysate (EBNH), a significant amount of water must be removed after hydrolysis to improve the product’s stability, extend shelf life, and reduce transportation and storage costs. This study investigates the application of cool-air and hot-air drying methods, with a particular focus on strategies suited for small and medium-sized enterprises (SMEs). Cool- air drying was performed at 17 °C using a fan and air conditioner, while hot-air drying was conducted at 55 °C and 65 °C using a dehydrator. The study evaluated drying time, as well as the quality, moisture content, nitrite levels, total sialic acid content, and antioxidant activity of EBNH produced by each method. The quality, cost, and feasibility of these methods were compared with freeze-drying and spray- drying techniques from previous studies. Results showed that higher temperatures and lower relative humidity improved drying efficiency, with hot-air drying at 65 °C requiring the shortest drying time. Chemical analysis revealed significant differences in nitrite and total sialic acid content: cold-air-dried samples had higher nitrite levels, while hot-air drying at 65 °C produced the highest total sialic acid content. Cost and feasibility assessments demonstrated that hot airdrying at 65 °C was the most efficient and cost- effective method. This method is especially advantageous for SMEs due to its balance of efficiency, affordability, and ease of implementation, making it ideal for smaller-scale operations.